Influence of ta'awun (mutual cooperation) in empowering social enterprises in the post pandemic covid-19 - Mhd. Sarif, Suhaimi (Zes Rokman Resources (2131022-P), 2022)
Malaysia has been consistent with its five-year economic development plan since 1955 with the First Malayan Plan (1955-1960) until 12th Malaysia Plan (2021-2025) to generate good economic growth, provide adequate employment, and sustain national unity. The foundation to achieve economic performance through mutual cooperation among people and economic participants has already been emplaced in Malaysia. The execution of the economic plan with bureaucratic approach reduces economic sustainability in the digital and competitive world. There is a need for a unified sharing economy through ta’awun (mutual cooperation) among social enterprises at the grass root levels to enhance economic resilience and sustain national unity. The study proposes that a unified sharing economy through ta’awun (mutual cooperation) social enterprises empowers social and economic resilience, enhances capacity building for supply-driven sharing economy and improves partnership and peace to achieve sustainable development. The study investigated factors that contributed to a unified sharing economy through ta’awun (mutual cooperation) social enterprises. The study used exploratory mixed methods. Firstly, the study conducted a qualitative focus group discussion (FGD) with two economic policymakers and five social enterprises owners. It distributed self-administered questionnaires among social enterprises to validate the unified sharing economy through ta’awun. The results of the focus group discussion and the survey emphasize that ta’awun (mutual cooperation) has empowered social enterprises through smart partnership, collaboration and cooperation with the grass root society, key players in the value chain, government agencies, non-government organizations, cooperatives, and local administrative bodies. This research provides a significant contribution to sustaining the social and economic resilience in the post-pandemic Covid-19.